Preservation Potential of Galangal Water Extract on Tofu - Alwani Hamad; Asmiyenti Djaliasrin Djalil; Tina Syah Putri; Dwi Hartanti (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Galangal (Alpinia galanga (L.) Willd.) has been long used for medicinal purposes. It showed promising effects on the food-spoilage microorganisms and is commonly used as spices in various cuisines. This study aimed to evaluate the microbial growth inhibitory activity and the preservation potential of galangal water extracts on tofu. The water extracts were prepared by infundation method in the concentrations of 5, 10, and 20%w/v. The phytochemical compounds in the extracts were screened as per standard methods. The tofu was preserved by immersion method for eight days under room temperature with an evaluation time point of two days. The microbial growth inhibitory activity was evaluated by indirect optical density (OD)-based enumeration, and the OD reduction by the extracts was calculated accordingly. The preservation potential was calculated from the changes of the physical characters on tofu evaluated by sensorial analysis. Galangal water extracts contained tannins and terpenoids. It concentration- dependently inhibited microbial growth on tofu, and the extract showed the best OD reduction at a concentration of 20%. It changed the color of tofu but maintained its texture. It also masked the odor of fresh tofu with the aromatic galangal scent. All three tested concentrations showed an equal preservation potential of 2 days. Our data suggested galangal water extract in the optimum concentration of 20% inhibited the microbial growth on tofu and potentially preserved it for two days. This moderate preservation effect might be attributable to its tannins and terpenoids content.